Joint Venture Strategy for Emerging Economy: Evidence From Russian Energy Sector - Panibratov, Andrei; Abramkov, Alexander (Organizations and Markets in Emerging Economies, 2012)
This paper investigates the strategies of global companies operating in power generation and supply, electrical equipment, and oil and gas industries in Russia. Russian energy sector has been considered by these companies as a huge and perspective and Russia has shown in the last two decades the greatest activity in the field of internationalization of major national industries through IJVs. Local joint ventures are therefore one of the cornerstones of these firms strategy in the respective energy sectors of Russia’s economy. These partnerships facilitate the entry process to Russia, raise an efficiency of post-entry operations, and prevent the state intervention in Russian operations of western companies.
Keywords: entry mode choice; international joint ventures; energy sector; Russia